La vestimenta tradicional montubia en el turismo cultural de la parroquia Pimocha - Rivas Moran, Alvaro Manuel (2018)
This project was carried out in the Parish of Pimocha belonging to the Babahoyo Canton of the Province of Los Ríos, recognized for its cultural tourism as: The Montubio Rodeo, Regatas, Myths and Legends, Patron Saint Festivities, among others, placing the research in the Clothing Traditional Montubia in Cultural Tourism, so that this allows visitors from different Cantons and Provinces of Ecuador to enjoy these cultural resources found in the locality. In spite of the existence of scarce tourist information and limited promotion, it will not be possible to have a tourist development. We can establish that through a better tourism promotion you can have a greater number of visitors as it will generate new jobs with an economic contribution to the residents, so tourists can enjoy their time of recreation, bone with friends or family.